Graphic Design Training Program Management During the Covid-19 Pandemic - Rusdin Djibu; Imam Shofwan; Gumpanat Boriboon (Journal of Nonformal Education, 2024)
Graphic design training is one of the training courses available at the Gorontalo Regency Work Training Center with the highest interest, so that it can help reduce the unemployment rate in Gorontalo Regency during the Covid-19 pandemic. The purpose of this study is to describe the management of graphic design training programs during the Covid-19 pandemic at the Gorontalo Regency Work Training Center. The type of research used is descriptive research with a qualitative approach. Data collection uses observation techniques, interviews, and documentation. The subjects are Tu Sub-District, Instructor, training manager and trainee. The validity of the data used is the triangulation of the source. The result of the research is the management of the graphic design training program at the Gorontalo Regency Work Training Center consisting of planning, organizing, implementing, supervising, assessment, and development referring to SKKNI that has been developed according to needs. The conclusion of this study is that the management of the graphic design training program at the Gorontalo Regency Work Training Center is carried out in accordance with the theory of experts. This research is carried out to provide understanding to the public regarding the correct management of training programs and in accordance with the theory of experts so that it can be used as input and development on training programs. The advice that can be given should the training manager be able to conduct further checks on the training facility and can cooperate with the company or form an independent business group to distribute graduates.